2008
DOI: 10.1021/jm7012216
|View full text |Cite
|
Sign up to set email alerts
|

Pradefovir: A Prodrug That Targets Adefovir to the Liver for the Treatment of Hepatitis B

Abstract: Adefovir dipivoxil, a marketed drug for the treatment of hepatitis B, is dosed at submaximally efficacious doses because of renal toxicity. In an effort to improve the therapeutic index of adefovir, 1-aryl-1,3-propanyl prodrugs were synthesized with the rationale that this selectively liver-activated prodrug class would enhance liver levels of the active metabolite adefovir diphosphate (ADV-DP) and/or decrease kidney exposure. The lead prodrug (14, MB06866, pradefovir), identified from a variety of in vitro an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…LMV and ADV have liver/serum ratios of 0.007 and 0.38, respectively (Reddy et al, 2008). Liver/serum ratios for TDF and ETV could not be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…LMV and ADV have liver/serum ratios of 0.007 and 0.38, respectively (Reddy et al, 2008). Liver/serum ratios for TDF and ETV could not be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone glucuronide thus showed low potential for absorption in the upper gastrointestinal tract of rats, and hydrolyzable by the gut flora. A good example is provided by pradefovir (5.54), a prodrug currently in clinical trials as the cis-(2R,4S)-isomer shown here [85]. The drug was bound to a high-molecular dextran via a succinate linker, with the conjugate containing about one drug molecule for ca.…”
Section: Fig 525mentioning
confidence: 99%
“…On the other hand, pradefovir mesylate, a propylated adefovir that depends upon CYP3A mediated activation, looked promising in Phase 2 studies, but was put on hold because of tumor formation in animals (Reddy et al, 2008). The development of MIV210 (Michalak et al, 2009) has also been abandoned (Grogan, 2013).…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%